FEATURES OF THE RESETTLEMENT OF KYRGYZ IN UZBEKISTAN (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2026)
In this article the processes of settlement of Kyrgyz tribes in the territory of Uzbekistan, as well as the dynamics of their numerical growth from the end of the 19th to the beginning of the 21st century.
Keywords: nation, ethnic processes, ethnotoponym, clan, nomad, diaspora, pastoralist, ethnodemographic characteristics